Anemia and Red Blood Cell Transfusions, Cerebral Oxygenation, Brain Injury and Development, and Neurodevelopmental Outcome in Preterm Infants: A Systematic Review - Kalteren, Willemien S.; Verhagen, Elise A.; Mintzer, Jonathan P.; Bos, Arend F.; Kooi, Elisabeth M. W. (Frontiers in Pediatrics, 2021)
Background: Anemia remains a common comorbidity of preterm infants in the neonatal intensive care unit (NICU). Left untreated, severe anemia may adversely affect organ function due to inadequate oxygen supply to meet oxygen requirements, resulting in hypoxic tissue injury, including cerebral tissue. To prevent hypoxic tissue injury, anemia is generally treated with packed red blood cell (RBC) transfusions. Previously published data raise concerns about the impact of anemia on cerebral oxygen delivery and, therefore, on neurodevelopmental outcome (NDO). Objective: To provide a systematic overview of the impact of anemia and RBC transfusions during NICU admission on cerebral oxygenation, measured using near-infrared spectroscopy (NIRS), brain injury and development, and NDO in preterm infants. Data Sources: PubMed, Embase, reference lists. Study Selection: We conducted 3 different searches for English literature between 2000 and 2020; 1 for anemia, RBC transfusions, and cerebral oxygenation, 1 for anemia, RBC transfusions, and brain injury and development, and 1 for anemia, RBC transfusions, and NDO. Data Extraction: Two authors independently screened sources and extracted data. Quality of case-control studies or cohort studies, and RCTs was assessed using either the Newcastle-Ottawa Quality Assessment Scale or the Van Tulder Scale, respectively. Results: Anemia results in decreased oxygen-carrying capacity, worsening the burden of cerebral hypoxia in preterm infants. RBC transfusions increase cerebral oxygenation. Improved brain development may be supported by avoidance of cerebral hypoxia, although restrictive RBC transfusion strategies were associated with better long-term neurodevelopmental outcomes. Conclusions: This review demonstrated that anemia and RBC transfusions were associated with cerebral oxygenation, brain injury and development and NDO in preterm infants. Individualized care regarding RBC transfusions during NICU admission, with attention to cerebral tissue oxygen saturation, seems reasonable and needs further investigation to improve both short-term effects and long-term neurodevelopment of preterm infants.